A-AARNET'S Stakeholders' directory - Association for Strengthening Agricultural Research in Eastern and Central Africa (A-AARNET, 2007)
The A-AARNET'S (Association for Strengthening Agricultural Research in East and Central Africa (ASARECA) - Animal Agriculture Research Network) stakeholders' directory, the first of its kind, aims at compiling in a single document, addresses of key stakeholders interested in research and Development activities of the livestock industry in East and Central africa who are contributing or have potential to contribute to the achievement of A-AARNET mission, goal and strategic objective. It is designed to be used as an important tool to facilitate communication and dissemination of information between A-AARNET stakeholders within the region and beyond. This issue has 1013 contacts and is organised in alphabetical order under a country name.